Ocular Syphilis and Human Immunodeficiency Virus Coinfection Among Syphilis Patients in North Carolina, 2014–2016. Issue 2 (February 2019) - Cope, Anna B.; Mobley, Victoria L.; Oliver, Sara E.; Larson, Mara; Dzialowy, Nicole; Maxwell, Jason; Rinsky, Jessica L.; Peterman, Thomas A.; Fleischauer, Aaron; Samoff, Erika
Abstract : Background: Ocular syphilis (OS) has been associated with human immunodeficiency virus (HIV) coinfection previously. We compared demographic and clinical characteristics of syphilis patients with and without HIV to identify risk factors for developing OS. Methods: We reviewed all syphilis cases (early and late) reported to the North Carolina Division of Public Health during 2014 to 2016 and categorized HIV status (positive, negative, unknown) and OS status based on report of ocular symptoms with no other defined etiology. We estimated prevalence ratios (PR) and 95% confidence intervals (CI) for OS by HIV status. Among syphilis patients with HIV, we compared viral loads and CD4 cell counts by OS status. We compared symptom resolution by HIV status for a subset of OS patients. Results: Among 7123 confirmed syphilis cases, 2846 (39.9%) were living with HIV, 109 (1.5%) had OS, and 59 (0.8%) had both. Ocular syphilis was more prevalent in syphilis patients with HIV compared to HIV-negative/unknown-status patients (PR, 1.8; 95% CI, 1.2–2.6). Compared with other patients with HIV, the prevalence of OS was higher in patients with viral loads greater than 200 copies/mL (1.7; 1.0–2.8) and in patients with a CD4 count of 200 cells/mL or less (PR, 2.3; 95% CI, 1.3–4.2). Among 11 patients with severe OS, 9 (81.8%) were HIV-positive. Among 39 interviewed OS patients, OS symptom resolution was similar for HIV-positive (70.0%) and HIV-negative/unknown-status (68.4%) patients. Conclusions: Syphilis patients with HIV were nearly twice as likely to report OS symptoms as were patients without documented HIV. Human immunodeficiency virus–related immunodeficiency possibly increases the risk of OS development in co-infected patients. Abstract : Ocular syphilis is more prevalent in syphilis patients with human immunodeficiency virus, particularly those with unsuppressed viral loads or low CD4 counts. Complaints of ocular symptoms may help detect previously undiagnosed human immunodeficiency virus.Supplemental digital content is available in the text.